Chapter Burladores e Convitati a Napoli tra Sei e Settecento, da Perrucci ad Abri (e oltre) - Cotticelli, Francesco (Studi e saggi, 2020)
This essay provides a comparison of select testimonies of the enduring tradition of Convitato di pietra (The Stone Guest) in Central and Southern Italy from the late 17th to the early 19th century. The text by Perrucci, the scenario from the Casamarciano collection, the anonymous revision located in the Italian Castle Archive at the Beinecke Library at Yale, and Abri's opera tragica (which relies significantly on Perrucci's setting) testify to the longevity of this plot - as well as of the Spanish repertoire - on the stage, in spite of notable changes, which reveal dramatic transformations in taste and sensitivity on the part of theatre practitioners and the audience.